2018
DOI: 10.1177/0300060517751452
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in patients with coronary artery disease: A literature review

Abstract: ObjectiveCognitive function impairment is a well-documented complication of cerebrovascular disease (CBVD). Less is known about what factors affect the deterioration of cognitive function in patients with coronary artery disease (CAD). The aim of this review is to explore recent studies investigating factors associated with cognitive function in patients with CAD.MethodsStudies published from 2010 to 2016 were identified through a systematic search of MEDLINE/PubMed and were included if they addressed factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 78 publications
0
13
0
1
Order By: Relevance
“…In the general population, CAD or myocardial infarction is associated with poorer general cognition and loss of verbal fluency, but the pathogenetic mechanism of that association remains elusive (Burkauskas et al 2018;Sundbøll 2018). CAD per se may lead to AF and heightened platelet activation, which, in turn, might trigger perivascular inflammation in the brain (Burkauskas et al 2018;Frazier et al 2014).…”
Section: Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, CAD or myocardial infarction is associated with poorer general cognition and loss of verbal fluency, but the pathogenetic mechanism of that association remains elusive (Burkauskas et al 2018;Sundbøll 2018). CAD per se may lead to AF and heightened platelet activation, which, in turn, might trigger perivascular inflammation in the brain (Burkauskas et al 2018;Frazier et al 2014).…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…In the general population, CAD or myocardial infarction is associated with poorer general cognition and loss of verbal fluency, but the pathogenetic mechanism of that association remains elusive (Burkauskas et al 2018;Sundbøll 2018). CAD per se may lead to AF and heightened platelet activation, which, in turn, might trigger perivascular inflammation in the brain (Burkauskas et al 2018;Frazier et al 2014). Overall, it is estimated that cART-treated PLHIVs are at 1.5-fold higher risk of clinical and subclinical CAD, with men having a lower relative risk (1.12) than women (1.99), compared to HIV-negative individuals (Boccara et al 2013;Baldé et al 2019).…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Interestingly, the mediating effect of plasma BDNF on platelet activity related cognitive decline was significantly lower in CAD patients than in subjects without CAD. Knowing that patients with CAD are at higher risk of cognitive impairment ( 39 ), the mechanisms behind this weakened protective effect of BDNF on platelet-related cognitive deterioration is worthy of further investigation. Future studies should examine in vitro the content and release of BDNF from platelets isolated from CAD and non-CAD individuals, to have a better understanding of mechanisms regulating platelet BDNF secretion in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Post-hoc meta-regression analyses showed that the association between CAD and cognitive decline was unchanged after adjusting for risk factors such as diabetes, hypertension, and dyslipidemia, suggesting that this association cannot be solely explained by cardiovascular risk factors [17]. A systematic review identified CABG, apolipoprotein E4, left ventricular ejection fraction, medication use, and hormones and biomarkers as predictors of cognitive decline in patients with CAD [30].Conversely, a prospective longitudinal study found no significant differences in long-term cognitive outcomes among CAD patients treated surgically with on-pump CABG (n = 152) or off-pump CABG (n = 75)) or non-surgically (n = 99) [6]. This is consistent with our results from univariate analysis.…”
Section: Discussionmentioning
confidence: 99%